A micrograting sensor for DNA hybridization and antibody human serum Albumin-Antigen human serum albumin interaction experiments - Chathirat, Naphat (2011)
A biosensor structure comprising silicon nitride (Si3N 4) micrograting arrays coated with a spin-on-glass (SOG) material was investigated. This grating structure was located on a silicon groove, which was etched by a deep reactive ion etching (DRIE) process. The biosensor was used as a specific detector of DNA molecules and antibody-antigen interactions. In our DNA sensing experiments, the first step was the activation of the grating surface with amine functional groups, followed by attachment of a 23-base oligonucleotide probe layer for hybridization with a complementary target DNA. The sensing device was tested for detecting specific antigen/antibody interactions for human serum albumin (HSA) and antigen bovine serum albumin (BSA). The readout system consisted of a white light lamp that illuminated a small spot on the grating surface at normal incidence through a fiber optic probe with a spectrometer used to collect the reflected light through a second fiber. We show that these sensing devices have the capability to detect DNA as well as antigen-antibody binding for HSA. The detection sensitivity for HSA was better than that for DNA mainly owing to the larger size and concomitant refractive index changes upon binding to the sensor. We show that it is possible to quantify the amount of biomolecules bound to the grating surface by measuring the wavelength shift of the reflectance spectra upon exposure to the samples.